Personification of mental concepts - Nizhehorodtseva-Kyrychenko, Larysa; Ніжегородцева-Кириченко, Лариса (Східноєвропейський національний університет імені Лесі Українки, 2015)
The article presents a brief excursus of linguistic and cognitive reasoning concerning the personification of the basic lexical units of the lexical-semantic field “Intellectual activity”. Personalization process implements an intrinsic property of metaphors, that is the property of anthropocentrism. It must be mentioned that the content of conceptual personification differs because while transforming personally identifiable object in a new status, it presents deeper comprehention. The article also summarizes the relationship between metaphorical shift and personification. Personification is a subtype of the metaphor, the essence of which is to express the transfer of characteristics of a living object to an inanimate object. The article also highlights the universal mechanism of personification that relates ideas, abstractions and inanimate objects with human nature, character, or feelings; representation of imaginary beings or things like having a human character, intellect and emotions. In the focus of analyses there are verbalized concepts of mind, memory, thought, soul, spirit, wisdom, which constitute the basic parcel of lexical-semantic field “Intellectual activity”. Verbalized abstract concepts that relate to intellectual activity, are often targeted to personification process that could not go unnoticed in lexical studies. Представлено короткий екскурс лінгво-когнітивних міркувань щодо персоніфікації лексичних одиниць лексико-семантичного поля «Інтелектуальна діяльність». Процес персоніфікації реалізує внутрішню властивість метафори, яка полягає в антропоцентричності. У змістовному відношенні концептуальна персоніфікація відрізняється тим, що, переводячи персоніфікований об’єкт в новий статус, вона дозволяє глибше його осмислити. Також коротко висвітлюється взаємозв’язок метафоричних зрушень і персоніфікації, універсальний механізм персоніфікації, яка співвідносить ідеї, абстракції та неживі об’єкти з людською сутністю, характером, почуттями, уявлення уявних істот або речей, які мають людський характер, інтелект і емоції. За численними фактами персоніфікації стоїть складна лінгвістична реальність, яка потребує спеціального дослідження та пояснення. У фокусі уваги знаходяться вербалізовані концепти mind, memory, thought, soul, spirit, wisdom, які складають базові парцели лексико-семантичного поля «Інтелектуальна діяльність». Вербалізовані абстрактні концепти, які співвідносяться з інтелектуальною діяльністю, часто стають об’єктами процесу персоніфікації, що не могло залишитися непоміченим у лексичних дослідженнях.
Персоніфікація ментальних концептів
Keywords: lexical-semantic field; cognitive linguistics; intellectual activity; verbalized concept; personification; персоніфікація; лексико-семантичне поле; інтелектуальна діяльність; когнітивна лінгвістика; концептуальна структура; персоніфікація